General anesthesia with remimazolam for a pediatric patient with MELAS and recurrent epilepsy: a case report - Yusuke Yamadori; Yuki Yamagami; Yukihisa Matsumoto; Mari Koizumi; Akiyo Nakamura; Daiskuke Mizuta; Kyoko Yasuda; Gotaro Shirakami (JA Clinical Reports, 2022)
Abstract Background Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) is a mitochondrial disease. We report here the safe use of remimazolam in a pediatric MELAS patient. Case presentation A 10-year-old girl (118 cm, 16 kg) was scheduled for an open gastrostomy to improve nutrition and epileptic seizure control. We induced and maintained general anesthesia with remimazolam, remifentanil, fentanyl, and rocuronium. We also performed a bilateral subcostal transversus abdominis plane block before the surgery. The surgery finished uneventfully. After we discontinued remimazolam administration, the patient woke up immediately but calmly without flumazenil. Epileptic seizures did not occur during intra- and early post-operative periods. Conclusion Remimazolam enabled us to provide a pediatric MELAS patient with general anesthesia without causing delayed emergence or epileptic seizures.